Numerical Simulation of Directional Wave Hydrodynamic Forces: A Study of Cylinder Arrays - Salim, Siddique Mohamad Yatim (Universiti Teknologi PETRONAS, 2020)
Waves are among the dominant environmental forces that are imposed on offshore structures. In the design of offshore platforms, the wave and sea conditions are often idealized by Long-crested wave (LCW) models. However, in recent years researchers have found that long-crested waves are not representative of actual sea conditions which could result in the overestimation of wave forces on structural members. Short-crested waves (SCW) models which are multi-directional are believed to be better at accurately representing real sea conditions as oppose to long-crested wave models which only considers the propagation of waves in a single direction. Hence this paper aims to compare the hydrodynamic response of vertical cylindrical arrays subjected to long-crested waves and short-crested waves. Meanwhile, for each wave condition, studies on the hydrodynamic response of cylindrical arrays when different relative spacing and configuration are used were also performed.